Case Report: Two instances of lung metastasis in low-grade endometrial stromal sarcoma - Long, Anying; Tian, Xiaoxue; Li, Yao; Luo, Shuai; Wang, Jinjing (Frontiers in Oncology, 2025)
BackgroundLow-grade endometrial stromal sarcoma (LGESS) with pulmonary metastasis is a rare malignant mesenchymal tumor. LGESS is composed of cells resembling proliferative endometrial stromal cells. It grows slowly and has a favorable prognosis, but late - term recurrence and metastasis are common. Thus, long - term regular follow - up is needed, and the possibility of tumor recurrence or metastasis should be considered when lesions appear later.Case demonstrationCase 1: A 55-year-old woman underwent a total hysterectomy 11 years ago for adenomyosis. She was later diagnosed with low-grade malignant uterine stromal sarcoma. She was admitted to the hospital due to “discovery of a pulmonary nodule 5 days ago.” Chest CT showed a nodule in the outer basal segment of the left lower lobe of the lung. Subsequently, she underwent “a single-port thoracoscopic wedge resection of the left lower lung lobe and closed thoracic drainage.”The postoperative pathology confirmed a low-grade endometrial stromal sarcoma with lung mety -30astasis. At the initial staging, no lung metastasis was detected. After surgery, she underwent EBRT radiotherapy. During the 12 - month follow - up, no recurrence was observed. Case 2: A 46-year-old woman underwent a total hysterectomy for a uterine mass at an external hospital two months ago. The postoperative pathology diagnosed her with low-grade endometrial stromal sarcoma. She was admitted to the hospital due to “chest pain for two months.” Chest CT indicated a nodule near the pleura of the left lower lobe of the lung. Subsequently, “a biopsy of the left pleural nodule was performed,” and the postoperative pathology confirmed metastatic endometrial stromal sarcoma to the left pleura. At the initial staging, no lung metastasis was detected. After surgery, she underwent EBRT radiotherapy. During the 4 - year follow - up, no recurrence was observed.ConclusionsLow-grade endometrial stromal sarcoma (LESS) lung metastasis is common in middle-aged and elderly women. While the overall survival rate is good, patients with long-term recurrence or metastasis, especially those with localized or non-metastatic tumors, face a high risk of disease progression. Currently, there is no standardized chemotherapy regimen for this condition. We report two cases of LGESS pulmonary metastasis, analyzing clinical features, histological morphology, immunohistochemistry, and differential diagnosis to enhance understanding of this condition. Without a medical history, it is easy to misdiagnose, particularly in cases of LGESS, where atypical symptoms can lead to misdiagnosis. Regular follow-up, prompt diagnosis, and treatment are crucial for improving prognosis and survival.